Sports informatics : a new interdiscipline in sports science - Liu, S.; Song Q.; Zhang H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction With diverse applications of bioinformatics and computer technologies in health, fitness, and sports, a new interdisciplinary subject -- Sports Informatics (SI) is on the edge of formalization and accreditation. The purpose of this study is to define the concepts of SI and explore the context of core knowledge of SI. Methods Meta Data research method is used to analyse the literature data, which collected from Bioinformatics, Medical Informatics, Cognitive Science, Health fitness, Sports Training, Physical Education and Sports/Exercise Science. The major tools are supercomputer search engines with multi-lingual applications. Results As the assembled data analysis, we found the necessity of SI, which is an emphasis on practical technologies for the solutions on current complex health problems, fitness guidance and sports science developments. SI mainly uses computer technologies and computational biology methods to explore and manage data in health and sports setting. SI derives knowledge by mixing, matching, and selecting from bioinformatics, medical informatics, cognitive science, statistics and sports/exercise science. Discussion/Conclusions A typical operation of SI system will start from collecting subjects` physiological, psychological, fitness and specific sports motor skills data. These measurement data will be stored, retrieved and analysed by a large-scale database with Ad hoc data processing. Often, the data are collected and measured by today's advanced medical equipments with highly technical procedures and guidelines. SI data processing depends on advanced computer technologies, especially digitalized graphic technology. SI has an emphasis on application rather than theories development, which implements ArrayData for the following: 1) Elite athlete selection and performance predictions, sports injury protection and best training protocols; 2) Enlarge and enrich the knowledge context of health fitness and physical education; 3) Provide scientific methods in managing leisure and recreation activities as well as guiding exercise prescriptions; 4) Provide health guidelines for human/machine interface activities such as E-sports activities on the Internet. Sports Informatics contains a mixture of ingredients from many disciplines such as computational biology, mathematical modelling, biochemistry, physiology, psychology, cognitive science, biomechanics, sports training, sports assessments and computer information management. SI is a new applied science in health fitness and sports settings. We propose an organized effort in establishing the fledgling interdiscipline of sports informatics.